TANTANGAN PROFESI PENELITI: SATU STUDI KASUS PUSAT PENELITIAN DAN PENGEMBANGAN KESEJAHTERAAN SOSIAL - Jayaputra, Achmadi (Sosio Informa : Kajian Permasalahan Sosial dan Usaha Kesejahteraan Sosial, 2016)
Researcher is a functional position in the Ministry of Social Affairs. The existence of researchers has been recognized since 1985 and it was marked by the appointment of eight people to be functional researchers. Over the last thirty years, the number of researchers has been growing as the result of the increasing number of the government’s tasks. This study is to discuss the researchers who work in the governmental institution and whose duties and functions have been determined through the intitution’s policy based on the rules set out in 2015. The work unit formation of Research and Development Centre for Social Welfare (Puslitbangkesos) has ever been changed several times. Therefore, it contributes to the implementation of its activities. Its goal is to give the charge to face the mental revolution that has been declared nationally. The situation will be different from the previous one because next, each researcher will begin to improve his quality by looking at very rapid development of science and technology. Each researcher must pay attention to a professional work ethic, rules and norms as well as researcher’s ethics. It is time for the researchers to improve their quality in increasing their knowledge and their ability to uphold the values of honesty, responsibility and dignity. Keyword: challenges, profession, work ethic.